The complete mitochondrial genome of soft coral Sinularia penghuensis Ofwegen and Benayahu, 2012 (Octocorallia: Alcyonacea): the analysis of mitogenome organization and phylogeny - Chun-Yang Shen; Pei-Zheng Wang; Wei Xue; Zhao-Hui Liu; Jing-Yi Zhao; Xiao-Bo Tong; Chunwei Liu; Xiao-Fang Wu; Xiaonan Mao; Sihan Tian; Chunzheng Fu (Mitochondrial DNA. Part B. Resources, 2021)
The complete mitochondrial genome of Sinularia penghuensis was sequenced and analyzed using next-generation sequencing. The present mitochondrial genome was 18730 bp in length, containing 14 protein-coding genes (PCGs) (cox1-cox3.nad1-nad6, nad4L, atp6, atp8, cytb, and MutS), two ribosomal RNA genes (rRNAs) (12S and 16S), and one transfer RNA gene (Met-tRNA). The phylogenetic analysis of family Alcyoniidae revealed that S. penghuensis and Sinularia maxima cluster together. Five species in Sinularia reveals high identity in mitogenome sequences that the lowest variable sites (SNPs) were found between S. penghuensis and S. maxima.